1995
DOI: 10.2134/agronj1995.00021962008700030005x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Responses to Chloride in Maximum Yield Research

Abstract: Chloride nutrition of corn (Zea mays L.) was investigated to determine if Cl limits production in high‐yield environments. Experiments were conducted to evaluate the effects of Cl fertilization on a Freehold sandy loam (fine‐loamy, mixed, mesic Typic Hapludults) near Adelphia, NJ, using irrigation and intensive crop production practices. Corn was grown at 107 600 plant ha−1 with equidistant spacing. All plots received 454 kg K ha−1 using KOH, K2SO4, or KCl to establish five treatments: 0, 50, 100, 200, and 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Reported data on Cl-disease-interaction are not consistent. Results documented on corn (Heckman, 1995) showed that Cl fertilization was beneficial for sustaining higher yield potential and suppressing stalk rot severity. The role of Cl on controlling disease reaction was found to have an inhibitory effect in take-all root rot, induced by Gaeumannomyces graminis var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported data on Cl-disease-interaction are not consistent. Results documented on corn (Heckman, 1995) showed that Cl fertilization was beneficial for sustaining higher yield potential and suppressing stalk rot severity. The role of Cl on controlling disease reaction was found to have an inhibitory effect in take-all root rot, induced by Gaeumannomyces graminis var.…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between the response of crops grown under salt-stressed conditions and disease reaction has not received great attention from research workers. The available literature cited on this topic is only centered on the effect of CI fertilization on disease susceptibility in com (Heckman, 1995), barley (Grey and Mathre, 1988) and wheat (Engle and Grey, 1991), Except for the experimental data reported by Kostandi and Sohman (1993), the results documented on corn-smut disease [Ustilago maydis (DC), Corda] interaction is also limited. Therefore, this study was initiated to evaluate the differential response of divergent com genotypes to smut disease reaction in relation to salt tolerance and to provide further details on the role of plant C!…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que o cloro (Cl) é um elemento essencial ao desenvolvimento vegetal, atuando na fotossíntese (TAIZ; ZEIGER, 2004), bem como podendo afetar o potencial osmótico da planta (HECKMAN, 1995). Contudo os efeitos benéficos e modo de ação do NaOCl no cultivo in vitro de vegetais não estão bem elucidados, sendo foco para futuros estudos a serem desenvolvidos.…”
Section: -------------------------------------(%) -------------------unclassified
“…Corda, was markedly reduced under salt-stressed conditions, but the effects were relatively small in highly susceptible and resistant corn cuitivars and very substantial in the moderately susceptible ones. Results documented on cloride-disease interaction are inconsistent, varying from a positive response (Heckman, 1995;Sturz and Bemier, 1989) to negative or no effects (Enge! and Grey, 1991).…”
Section: Introductionmentioning
confidence: 99%